PHONOLOGICAL VARIATION OF TALIABU LANGUAGE DIALECTS - Ridwan Ridwan; Farida Maricar; Sunaidin Ode Mulae; Sherly Asriyani (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
This research aimed to describe the phonological variation of Taliabu language dialects. This research used a qualitative descriptive method. The technique of data collection was obtained by taking notes, records, and interviews. Data obtained was analyzed by the stages of reduction, presentation, conclusion, and verification data. The result of the research showed that Taliabu language had three dialects, namely Kadai, Siboyo, and Mange. Phonological variations of Taliabu language occurred in the three dialects comprise of vowel variations, namely /e/, /a/, and /o/. Beside the vowel variation, there is also variation of consonants such as /g/, /y/, /h/, /t/, /d/, / m/, /ŋ/, /b/, /p/, /k/, dan /r/ phonemes. Among the three dialects, one of them has high innovation namely Mange dialect, meanwhile, dialects have high phonological differences between Kadai and Mange dialects.